Translating stones: a corpus-based linguistic and lexicographic study in specialized terminology - Viviana Gaballo (Lexis: Journal in English Lexicology)
This study originated from the real-world need to provide a lexicographic reference work for the specialized field of stone processing. Very little is available on this specific niche of the lexicon. This contribution will offer lexicographers and terminologists a first insight into the identification and designation of materials, activities, and processes related to the quarrying and processing of stones. The study was conducted on the data collected to build a pair of comparable corpora, each containing a variety of texts – from brochures to technical specifications – in one of the source languages investigated: English and Italian. The methodology employed derives from the report on a Council of Europe project (see International Journal of Lexicography vol. 9, n. 3, 1996). To advance the inquiry, a number of term candidates were identified – based on the frequency and keyword lists generated from the corpora – and analysed in their contexts of use to eventually formulate hypotheses of equivalence in both languages. This work is the result of the growing convergence of different approaches to meaning, all harnessing corpus evidence.